Desenvolvimento de dispositivo original para medição e registro de ondas de corrente de descargas atmosféricas - Listz Simões de Araújo (2020)
The acquisition of lightning-current waveforms is important for providing parameters required for lightning-protection design and for estimating effects resulting from lightning events. Currently, building and maintaining research stations able to obtain lightning current waveforms from instrumented towers require high investments, which make impossible data acquisition from different places of a specific region. This doctoral project consisted in the design and development of a device for measuring and recording the waveform of the return stroke currents by means of the nearby electromagnetic field. The low-cost device based in DSP has the purpose of providing a consistent alternative to traditional systems of impulsive current measurements. Two measurement systems were developed, the main difference being the acquisition sensor of the induced voltage. One employs a loop antenna, while the other a Rogowski coil. Both systems include additional functionalities, such as remote access, self-test, data transfer, all of which can be controlled from the internet. The validation of the proposed systems was performed in two stages. The first one was based on laboratorial tests and the second one on the measurement of lightning currents at Morro do Cachimbo Station (MCS). In 2018, four devices were installed at MCS, three with a loop antenna and one with a Rogowski coil. These devices recorded the waveform of five first return currents of negative downward lightning that hit MCS instrumented tower. The results obtained by the developed systems were consistent with those provided by the traditional measurement system. As a sequence of the doctoral project, it is intended to build a network of several devices installed in different location in a region, which is determined by a radius of the 30 km, in order to obtain a relevant local database of parameters of lightning currents in a short period of time.